Microscopic understanding of exceptional orientation-dependent tensile and fracture responses of two-dimensional transition-metal carbides - Jhon, Young In; Han, Il Ki; Lee, Ju Han; Jhon, Young Min (Elsevier BV, 2022)
Two-dimensional (2D) materials have exceptional mechanical properties that are absent in conventional bulk materials due to their ultra-thin structure with ultra-high surface-to-volume ratio. Despite their great potential both for basic research and applications, however, deep understanding of fundamentally important orientation dependent mechanical responses of 2D materials have rarely been achieved. In this work, for the first time, we investigate the tensile mechanical response of 2D transition-metal carbides (MXenes) as gradually varying tensile direction by using reactive molecular dynamics simulations. Despite its highly bonded multi-atom-thick structure, MXene proves significantly stretchable (11-17%) for all directions with isotropic stiffness desirable for flexible/wearable applications, while exhibiting unusual characteristic fracture anisotropy. Noticeably, these mechanical features remained qualitatively the same regardless of presence/absence of surface termination. We discover that MXene has always fractured into zigzag-atomic edged fragments regardless of tensile direction and/ or surface termination. We reveal the detailed fracture mechanism and propose its generalization to other hexagonal 2D materials with validation for both pristine and surface-hydrogenated graphene nanosheets. Based on these findings, we finally present a physically robust, computationally efficient framework for fast and reliable prediction of MXenes' unique fracture anisotropy, showing excellent agreement with time-consuming simulation results and suggesting broad applicability to 2D material mechanics.